Optimizing Services at PDAM Tirta Darma Ayu in Indramayu Regency Based on Customer Needs - Afiffuin Afiffuin; Yanto Heryanto (Journal of Comprehensive Science, 2026)
Clean water services are essential public services that directly affect community welfare and quality of life. As a regional water utility company, PDAM Tirta Darma Ayu in Indramayu Regency faces challenges in ensuring reliable, responsive, and customer-oriented services, particularly in terms of water distribution, complaint handling, and consistent service quality. This study aims to optimize PDAM Tirta Darma Ayu services based on customer needs by evaluating service quality dimensions and identifying factors that hinder service effectiveness. This research employed a qualitative descriptive method conducted at PDAM Tirta Darma Ayu in Indramayu Regency, particularly in Bangodua District. Data were collected through in-depth interviews, field observations, documentation studies, and monitoring of customer interactions through the official Facebook platform of PDAM Tirta Darma Ayu. Data validity was ensured through triangulation techniques, while data analysis was conducted using descriptive analysis. The findings indicate that the tangible and empathy dimensions of service quality have been implemented effectively, supported by adequate facilities, professional personnel, and customer-oriented services. However, the reliability, responsiveness, and assurance dimensions still require improvement due to inaccurate water meter recordings, delayed responses to digital complaints, uncertainty regarding repair completion times, and customer concerns about water quality. The study concludes that PDAM Tirta Darma Ayu needs to strengthen technical accuracy, digital complaint management, service transparency, and customer communication systems to enhance customer satisfaction and public trust.